Inside vanguard : leadership secrets from the company that continues to rewrite the rules of the investing business - Ellis, Charles D. (McGraw Hill-Ascent Audio, 2022)
This rare intimate look at Jack Bogle and his world-changing investment organization provides invaluable lessons for investors, for business leaders, and for historians of finance One of the world's largest, fastest-growing, and most trusted investing institutions, Vanguard serves over 30 million clients, manages more than eight trillion dollars, and is an influential industry disruptor. Now, Charles D. Ellis reveals the story behind Vanguard's rise to the top of the investing world. Provided unprecedented access to Vanguard's leaders, including Bogle himself, Ellis explains why Bogle started Vanguard and how he developed it into an investment industry disrupter and, eventually, an industry leader. Along the way, you'll learn practical lessons about: active investing, index investing, ETFs, mergers, and building and running a business. Ellis includes in-depth interviews with the executives and key leaders of Vanguard, clear takeaways and lessons from their experiences, a primer on ETFs, and Jack Brennan's Leadership Principles. From the emergence of index funds to the success of exchange-traded funds, Inside Vanguard is a near-Shakespearian drama of individual human struggle and triumph.